Gambaran Quantitative Electroencephalography Pada Penderita Gangguan Kognitif Pascastroke di RSUP Dr. Mohammad Hoesin Palembang - Febrianto, Yohanes; Nindela, Rini; Harun, Yusril; Handayani, Sri; Legiran, Legiran (PERDOSNI, 2024)
Post-stroke cognitive impairment (PSCI) is one of the post-stroke complications that is often overlooked. Quantitative electroencephalography (QEEG) is an alternative examination in patients with PSCI. QEEG results of PSCI patients shows abnormalities in spectral power, coherence, power ratio, and peak alpha frequency (PAF). Aim: Knowing the QEEG characteristic in PSCI patients and the characteristic differences between the post stroke dementia (PSD) and post stroke cognitive impairment no dementia (PSCI-ND). This research is a descriptive study of PSCI patients at the RSMH Palembang from September-November 2023, followed by a QEEG examination. There were 31 patients who completed the research. There is higher median absolute and relative power delta and theta both per region and globally, decreased interhemsiferous coherence at F3-F4, P3-P4, O1-O2, T5-T6, C3-C4, increased delta alpha ratio and delta theta alpha beta ratio in the frontal region, as well as a decrease in peak alpha frequency in all regions. Patients with post-stroke dementia have more abnormality in relative global power, frontal DAR and DTABR, and PAF than patients with PSCI-ND Stroke can cause slowed conduction along the cortical-subcortical pathways, disruption of cholinergic pathways and impaired communication in various parts of the brain. This condition can cause a decrease in alpha power as an important wave in cognitive function and an increase in delta power in various brain regions. A decrease in the fast wave spectrum and an increase in the slow wave spectrum may lead to decreased cognitive function as seen in patients with PSCI Post stroke cognitive impairement, Power ratio, Quantitative electroencephalography, spectral power.